Animal Abuse: Helping Animals and People 2013
DOI: 10.1079/9781845939830.0104
|View full text |Cite
|
Sign up to set email alerts
|

Sheltering animals & families together (SAF-T) TM : working together to protect families and pets from abuse.

Abstract: This chapter discusses the main points mentioned in the Sheltering Animals and Families Together (SAF-T) start up manual. Highlights focused on the role of veterinarians in SAF-T programme (created since pets are accepted as part of the family and that pets can be targets of domestic violence).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This quote illustrates the devastating reality that IPV and animal abuse rarely occur in isolation from one another (Animal Protection Services of Saskatchewan [APSS], 2016; Ascione, 2000; Levitt, Hoffer, & Loper, 2016; Phillips, 2015). In particular, research shows that perpetrators of violence target companion animals or livestock as a method of control or revenge over their human victims (APSS, 2016; Ascione, 2000; Phillips, 2015). Companion animals are typically smaller animals, such as cats, dogs, birds, gerbils, or fish.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…This quote illustrates the devastating reality that IPV and animal abuse rarely occur in isolation from one another (Animal Protection Services of Saskatchewan [APSS], 2016; Ascione, 2000; Levitt, Hoffer, & Loper, 2016; Phillips, 2015). In particular, research shows that perpetrators of violence target companion animals or livestock as a method of control or revenge over their human victims (APSS, 2016; Ascione, 2000; Phillips, 2015). Companion animals are typically smaller animals, such as cats, dogs, birds, gerbils, or fish.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Ascione (2000) found this to be true for up to 40% of IPV survivors. This is often because companion animals provide invaluable emotional support (Ascione et al, 2007; Flynn, 2000; Phillips, 2015). Approximately 71% of those who reported not seeking refuge from IPV reported that their perpetrator exerted or threatened abuse to a companion animal, through such methods as threat, injury, or killing (Ascione, Weber, & Wood, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to these situations, domestic violence shelters are developing collaborative foster care programs with local animal welfare agencies to provide off-site “safe havens” for the animal survivors, thereby removing one barrier that prevents families from escaping abuse (Ascione, 2000 ). More recently, a program called SAF-T—Sheltering Animals and Families Together—is helping more than 200 domestic violence shelters in the U.S. and other countries build co-sheltering facilities for pets to keep all family members together and safe (Phillips, 2019 ). Grant funding is available to help shelters with capital costs and survivors with veterinary and boarding expenses (National Link Coalition, 2019d ).…”
Section: Incorporating These Dynamics Into Career Opportunities Beyonmentioning
confidence: 99%
“…Social workers can coordinate veterinary and foster care for the animals and advocate for pet-friendly co-shelters for the homeless much as has been done in domestic violence shelters (Phillips, 2019 ). Social workers can participate in such programs as the Street Dog Coalition, operating in 30 states, in which social work, veterinary and medical school students host clinics and provide resources to help the pets of homeless pet owners.…”
Section: Incorporating These Dynamics Into Career Opportunities Beyonmentioning
confidence: 99%
“…DV shelter organizations should continue to build collaborative networks with local animal support services, and develop safe sheltering options for families exposed to IPV and their pets. Specifically, our finding that weapons (i.e., firearms) were frequently used during animal maltreatment, and that women and children’s concern for and emotional attachment to companion animals delayed or impacted safety planning decisions, indicates that shelter services should consider the value of developing co-sheltering programs, such as Sheltering Animals and Families Together (SAF-T; Phillips, 2015), which allow families and companion animals to stay together while in shelter. Advocates and counselors can also help survivors address potential feelings of guilt and/or responsibility for maltreatment of the animal in the context of IPV.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%